Effective weight-reduction- and crashworthiness-analysis of a vehicle's battery-pack system via orthogonal experimental design and response surface methodology. (October 2021) - Xiong, Yue; Pan, Yongjun; Wu, Lei; Liu, Binghe
Highlights: Different ADSSs and wall thickness values are designed for the BPE components to minimize its weight. An OED method is introduced to establish an RSM model of the BPE. Lightweight design of the BPE is performed based on a multi-island genetic algorithm and the RSM model. The crashworthiness of the optimized BPS (including battery modules) is verified numerically. Abstract: Battery pack systems (BPSs) are one of the most critical systems in electric vehicles. They have a high impact on the final range of any electric vehicle and also affects a vehicle's safety level. This means a lightweight battery pack enclosure (BPE) design is desirable for maintaining a long range and good safety level, but a good crashworthiness performance also needs to be sustained. In this study, a novel procedure which enables a significant weight reduction of a battery-pack system is proposed. The approach is based on orthogonal experimental design (OED), response surface methodology (RSM), and a multi-island genetic algorithm. First, a nonlinear finite element model of a BPS (including battery modules) which considers the complexity of the structure was developed. The finite element model was verified by comparing the constrained modal analysis results with bench test results. Second, as part of the random vibration analysis, an OED method was introduced to build a quadratic RSM model. This model was used in conjunction with a multi-island genetic algorithm to perform effective weight reduction of the BPE. Finally, the crashworthiness of the optimized structure was numerically verified in terms of crash and crush simulations. The crash and crush impacts on the battery modules were investigated and prototypes of the optimized BPE were fabricated for future validation via physical tests. These results showed that the optimized BPE was 11.73% lighter than an unoptimized BPE and that enhanced crashworthiness was achieved. The proposed weight reduction procedure can be used to quickly determine the material and thickness of the main components of a BPE.